2005
DOI: 10.1002/ajmg.a.30882
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the clinical phenotype associated with OPHN1 mutations based on the clinical and neuropsychological evaluation of three families

Abstract: Recent reports have demonstrated that mutations in the OPHN1 gene were responsible for a syndromic rather than non-specific mental retardation. Abnormalities of the posterior fossa with cerebellar hypoplasia have been demonstrated in all male patients reported to date. We report here a new family with X-linked mental retardation due to mutation in OPHN1 and present unpublished data about two families previously reported, concerning the facial and psychological phenotype of affected males and carrier females. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 11 publications
3
23
0
Order By: Relevance
“…[4][5][6][22][23][24][25][26][27][28][29] All but one of the reported mutations are thought to result in premature stop codons and the absence of any OPHN1 protein. As the exception, Pirozzi et al 6 reported on a 2-bp OPHN1 deletion that abolishes a donor splicing site in intron 7 of OPHN1 in an Italian family segregating with ID and cerebellar hypoplasia.…”
Section: Exonmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][22][23][24][25][26][27][28][29] All but one of the reported mutations are thought to result in premature stop codons and the absence of any OPHN1 protein. As the exception, Pirozzi et al 6 reported on a 2-bp OPHN1 deletion that abolishes a donor splicing site in intron 7 of OPHN1 in an Italian family segregating with ID and cerebellar hypoplasia.…”
Section: Exonmentioning
confidence: 99%
“…3,5,[23][24][25]27 The absence of other discernible symptoms and signs among ID patients with OPHN1 mutations suggests that an OPHN1 deficiency may be compensated by functional redundancy with other Rho GTPase-related proteins in non-affected tissues. Alternatively, the structures of the brain where OPHN1 is expressed are characterized by high levels of plasticity and the brain may be more sensitive to loss of OPHN1 compared with other tissues.…”
Section: Exonmentioning
confidence: 99%
“…Des Portes et al (2004) carefully investigated the brain structure of these patients and described a specific dysgenesis of the cerebellar vermis and some diffuse cortico-subcortical atrophy. Thirteen more pedigrees with mutations in OPHN1 have been reported since 1998 (Tentler et al, 1999;Bergmann et al, 2003;Philip et al, 2003;Chabrol et al, 2005;Zanni et al, 2005;Menten et al, 2007;Froyen et al, 2007;Madrigal et al, 2008;Al Owain et al, 2010). All the investigated patients had some degree of cerebellar hypoplasia with the exception of a female patient with mild mental retardation (IQ~75) in the pedigree reported by Bergmann et al (2003).…”
Section: Discussionmentioning
confidence: 97%
“…The same gene was interrupted in a female patient with an X;12 balanced translocation (Bienvenu et al, 1997;Billuart et al, 1998). After these two reports, 13 more pedigrees have been reported with mutations in OPHN1 (Tentler et al, 1999;Bergmann et al, 2003;Philip et al, 2003;Chabrol et al, 2005;Zanni et al, 2005;Menten et al, 2007;Froyen et al, 2007;Madrigal et al, 2008;Al Owain et al, 2010). All OPHN1 mutations identified to date eventually cause loss of function of the oligophrenin 1 protein.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoplasia of the pons and cerebellum with progressive volume loss can be characteristic of congenital disorder of glycosylation type 1a [Grünewald, 2009], but many other manifestations differ and isoelectric focussing of transferrin yielded normal results. Mutations in OPHN1 (OMIM 300486) cause an X-linked intellectual disability-small cerebellum syndrome which sometimes is associated with macrocephaly [Chabrol et al, 2005], but the overall phenotype is milder and females carriers are usually asymptomatic Please note the thick cranial vault and slightly sclerotic cranial base, the poorly modeled phalanges and metacarpals, the shortening of the middle phalanges of the fifth fingers and the broad proximal and medial phalanges and small terminal phalanges of the fifth toes.…”
Section: Discussionmentioning
confidence: 99%